Maturation of Cardiac Energy Metabolism During Perinatal Development - Piquereau, Jérôme; Ventura-Clapier, Renée (Frontiers in Physiology, 2018)
As one of the highest energy consumer organ in mammals, the heart has to be provided with a high amount of energy as soon as its first beats in utero. During the development of this organ, energy is produced within the cardiac muscle cell depending on substrate availability, oxygen pressure and cardiac workload that drastically change at birth. Thus, energy metabolism relying essentially on carbohydrates in fetal heart is very different from the adult one and birth is the trigger of a profound maturation which ensures the transition to a highly oxidative metabolism depending on lipid utilization. To face the substantial increase in cardiac workload resulting from the growth of the organism during the postnatal period, the heart not only develops its capacity for energy production but also undergoes a hypertrophic growth to adapt its contractile capacity to its new function. This leads to a profound cytoarchitectural remodeling of the cardiomyocyte which becomes a highly compartmentalized structure. As a consequence, within the mature cardiac muscle, energy transfer between energy producing and consuming compartments requires organized energy transfer systems that are established in the early postnatal life. This review aims at describing the major rearrangements of energy metabolism during the perinatal development.